The blood bay colt - Farley, Walter 1915- (Random House, 1950)
A boy is entrusted to attend the birth, train, and drive a blood bay colt that is the great hope of an aging reinsman who refuses to be reconciled to the fact that sulky-racing has moved from the county fair to the big night time, moneymaking raceways.